Impact of CdCl2 treatment in CdTe thin film grown on ultra-thin glass substrate via close spaced sublimation - Amin N.; Karim M.R.; ALOthman Z.A. (MDPI AG, 2023)
In this study, close-spaced sublimation (CSS) grown cadmium telluride (CdTe) thin films with good adhesion to 100m thin Schott D263T ultra-thin glass (UTG) were investigated. Cadmium chloride (CdCl2) treatment in vacuum ambient was executed to enhance the film quality and optoelectrical properties of CdTe thin film. The post-deposition annealing temperature ranging from 360-420 C was examined to improve the CdTe film quality on UTG substrate. Various characterization techniques have been used to observe the compositional, morphological, optical, as well as electrical properties. Scanning electron microscopy (SEM) verified that the CdTe morphology and grain size could be controlled via CdCl2 treatment temperature. Energy Dispersive X-Ray Analysis (EDX) results confirmed that the annealing temperature range of 375-390 C yielded the stoichiometric CdTe films. UV-Vis analysis estimated the post-treatment bandgap energy in the range of 1.39-1.46 eV. Carrier concentration and resistivity were obtained in the order of 1013 cm-3 and 104 cm, respectively. All the experimental results established that the CdCl2 treatment temperature range of 390-405 C might be considered as the optimum process temperature for the deposition of CdTe solar cell on UTG substrate in close-spaced sublimation (CSS) method. 2021 by the authors.